Pengaruh Perasan Daun Ubi Kayu (Manihot esculenta Crantz) terhadap Mortalitas Keong Mas (Pomacea canaliculata L). - Pagarra, Halifah (bionature, 2009)
This study was an experimental study, aimed to determine the effect of cassava (Manihot esculenta Crantz) leaf extract on golden apple snail (Pomacea canaliculata L) mortality and to determine the leaf extract concentration that provide best effect on golden apple snail mortality. The variables of this study were cassava leaf extract as independent variable and golden apple snail mortality as dependent variable. This study used complete random design, consisted of 6 treatments: K0 (without cassava leaf extract application), K1 (50 g/L), K2 (75 g/L), K3 (100 g/L), K4 (125 g/L) and K5 (150 g/L), each treatment had three repetitions using 10 snails in every treatment, so the total number of snails used was 6 x 3 x 10 = 180. The test performed in two steps, pilot test and real test to observe the LC50 and LT50 value with observation parameters including rate and number of golden apple snail mortality for 48 hours observation. The obtained data were analyzed using variance analysis FÎ± = 0,05 and probit analysis, continued with BNT Î± = 0,05. It was observed that cassava leaf extract had significant effect on golden apple snail mortality and mortality rate began at 4 hour application. Result of BNT Î± = 0.05 providing the best effect was concentration of 100 g/L (K3). LT50 value for cassava leaf extract was at 57.280 hours, with regression slopeÂ  Y = -0,506 + 3,132X. Whereas the LC50 value was 88.716 g/L with regression slope Y = 7,997 â€“ 1,762X. Keywords: golden apple snail (Pomacea canaliculata L)., Manihot esculenta Crantz and mortality